Effect of Al2O3 addition on the microstructure and oxidation behavior of SiC coating prepared by pack cementation on C/C composites. Issue 20 (15th October 2021) - Liu, Yangyang; Miao, Qiang; Liang, Wenping; Lin, Hao; Ma, Hanchun; Shi, Weiwei; Xu, Xiao
Abstract: The study addresses the effects of Al2 O3 on the SiC coating fabricated by pack cementation by preparing coatings with different Al2 O3 contents on C/C composite. After the in-depth analysis of various characterization results, including XRD, SEM, EDS, and XPS, the competition brought by Al2 O3 between enhancing coatings qualities and affecting oxidation behaviors was revealed. One insight into the microstructure of as-prepared coatings is that Al2 O3 could boost internal exchange and the diffusion of parent materials, which is conducive to resisting oxidation by improving the qualities of the layers. Another insight about the coating oxidation is obtained from the SiC–Al2 O3 volatility diagram, where the multiple roles of Al2 O3 plays in the transition of oxidative mechanisms are elucidated. The beneficial impact that stables the oxide layer and reduces the coating consumption takes the upper hand comparing to the adverse effect, including breaking the structure of SiO2 .